Construir e reconstruir: o literário na subjetividade do leitor em transformação - Freitas, Rafael da Cruz (2025)
This dissertation investigates the role of literary text in the formation of readers in public high school, focusing on the subjective experience of reading and the processes of construction and reconstruction of interpretations. The research, of an applied and exploratory nature, with a participant action-research approach, involved first-year high school students from a state school. The study analyzed the place of Literature in Brazilian official documents, such as the BNCC and the Referencial Curricular Gaúcho (RCG), pointing to a devaluation of the Literature component, which is frequently grouped with Portuguese Language and treated as an object for the development of linguistic skills, to the detriment of its potential as a subjective experience. The research proposed and applied three Reading Experiences, based on the theoretical assumptions of Judith A. Langer on the construction of representations, Jorge Larrosa on experience, and Rildo Cosson on literary literacy. The Reading Experiences used works by Conceição Evaristo, Elza Soares, and Racionais MC’s, seeking to promote a connection between the texts and the students' reality. The analysis of the data collected through questionnaires and reading diaries was conducted from the perspective of Carlo Ginzburg's Indiciary Paradigm, seeking to identify signs of subjectivity in the participants' responses. The results indicate that literary reading, when approached as an experience that considers the subjectivity of the reader, can significantly influence their processes of interpretation and understanding of the world. The dissertation concludes that it is essential to rethink the teaching of Literature in high school, shifting the focus from the mere transmission of content to the promotion of meaningful reading experiences that allow students to construct and reconstruct meanings about themselves and the world, developing literary literacy that extends beyond the school walls.